Implementation of Blockwork System in Malaysia - Nor Azhari Azman, Mohamed; Afendi Bahari, Farul; Kusumawardani, Rini; Tze Kiong, Tee (KnE Social Sciences, 2019)
Industrialised Building System or IBS is a method to accelerate the process of construction through prefabricated concept where each component will be built first in the component manufacturing plant. There are six categories of IBS introduced by CIDB and one of them is a system block work. The block system has several types of components under this category include the interlocking block-concrete masonry unit (CMU) and lightweight concrete blocks. Block work system introduced to replace the use of conventional bricks to accelerate the construction process and reduce construction costs. However, acceptance of the system to be less favorable than the use of conventional bricks. Statistics show there are only 31 manufacturer across Malaysia. Therefore, this study aims to identify the extent of implementation of the system of block work in Malaysia to contribute in the construction sector. This study used qualitative methods, namely through interviews and focus groups. The findings revealed that there are differences between the application methods IBS system block and conventional brick in terms of type of work performed, the number of working days and the cost of construction. Implementation of the system blocks are also influenced by three factors: the skills of workers, quality of components and component types in use. With a wide exposure is expected to expand the implementation of the system blocks in Malaysia. Keywords: Industrialised Building System; block work system; brick; Construction Industry Development Board; Concrete Masonry Unit